Comparative study of quality of life 9 months post-COVID-19 infection with SARS-CoV-2 of varying degrees of severity: impact of hospitalization vs. outpatient treatment - Maslova, Olga; Vladimirova, Tatiana; Videnin, Arseny; Gochhait, Saikat; Pyatin, Vasily (Frontiers in Sociology, 2023)
Purpose. This experimental study was performed in the post-COVID-19 paradigm to identify the dependence of quality of life after 9 months on the severity of the SARS-CoV-2 infection in two conditions of hospitalization (use/non-use of medical oxygen) and outpatient treatment. Methods. Using the EQ-5D-5L Quality of Life tests and the PSQI in the form of a survey of respondents 9 months after a previous SARS-CoV-2 infection severity. Results. We identified a clear difference in the quality of life on the 100-point scale EQ of the EQ-5D-5L test, which was significantly lower for 9 months post-COVID-19 in group 1 of respondents (n=14) who had suffered SARS-CoV-2 infection in the conditions of hospitalization and medical oxygen use compared to the respondents who did not patients who were treated on an outpatient basis (n=13) (H=7.08 p=0.029). There were no intergroup differences in quality of life indicators between hospitalized patients (Group 2, n=12) and groups 1 and 3. PSQI showed that "mobility", "self-care", "daily activities", "pain/discomfort", and "anxiety/ depression" do not have inter-group differences, and therefore they are not associated with the severity of SARS-CoV-2 infection. On the contrary, the respondents demonstrated significant inter-group differences (H=7.51 p=0.023) and the interdependence of respiratory difficulties with the severity of clinically transmitted SARS-CoV-2 infection. It was also established the significant differences in the values of sleep duration, sleep disorders and daytime sleepiness indicators between the three groups of respondents, which indicates that influences and severity. The responses of the PSQI test "bedtime" (H=6.00 p=0.050), "wake-up time" (H=11.17 p=0.004) significantly differed between groups 1 and 3 of respondents, while after 9 months of post-COVID-19, respondents in group 1 went to bed at a later time (pp=0.02727) and woke up later (p=0.003) than the respondents in group 3. Conclusion. This is the first study in the current literature to report on the quality of life of respondents 9 months post-COVID-19 that was shown between the cohorts of hospitalized and treated with medical oxygen and the cohorts of outpatient patients. Post-COVID-19 quality of life indicators depending on SARS-CoV-2 severity can help stratify patients for targeted post-COVID-19 rehabilitation.